Divergência interpopulacional e interespecífica e processo seletivo atuante nos genes ortólogos a fruitless e Odysseus em Drosophila mojavensis e D. arizonae - Santos, Wellington dos [UNESP] (2014)
Despite having been intensively studied, many questions about the process of speciation remain unanswered, especially regarding genetic changes that lead to reproductive isolation. In this study we analyzed two genes candidates for speciation genes, fruitless (fru) and Odysseus (OdsH) in two closely related cactophilic Drosophila species, D. mojavensis and D. arizonae, which diverged from a common ancestor less than 1 million years ago. The fru gene plays a predominant role in the specification of the potential for sexual behavior of Drosophila male, thus influencing the pre-zygotic isolation. OdsH, a gene with a homeodomain that has undergone rapid evolution in the melanogaster subgroup of species, has been associated to hybrid sterility in Drosophila. Sequences of these two genes, known to be variable in Drosophila and other insects, were amplified and sequenced in four strains of D. mojavensis and two of D. arizonae. Analyses of diversity, selection tests and phylogenetic analyses were performed. Both genes show low diversity between the sequences from the two species, which is consistent with the recent divergence between them. The selection tests performed for the sequences showed that the fragments analyzed of both genes are under purifying selection, which is consistent with data in other Drosophila species considering the fru gene, but is different from data for OdsH in species of the subgroup melanogaster, in which is under positive selection. Phylogenetic relationships reconstructed for the sequences of the two genes, as well as networks of haplotypes allowed to make inferences about the evolutionary history of species and populations. Analyzes of Neighbor Joining and Maximum Likelihood clustered all the sequences of D. mojavensis in a monophyletic clade, as well as the sequences of each of its strains, reinforcing the classification of subspecies for the populations from where they were colected. However, the monophyly...